GAYA KEPEMIMPINAN DAN KEPUSAN KERJA DI PERUM PERUMNAS REGIONAL III - Lia Kusuma Pratiwi; Herwindo Haribowo (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2013)
Abstract The aim of this study is to know the difference of leadership styles and job satisfaction in PERUM PERUMNAS REGIONAL III. The research was held in PERUM PERUMNAS REGIONAL III, Jakarta on June – September 2013. This research used quantitative ex-post facto research method. Data were collected using scale of LBDQ XII (Leadership Behavior Description Questionnaire) and scale JSS (Job Satisfaction Survey), were assessed among 129 outpatients. Statistical analysis was done using the Analysis of Varians with SPSS version 17.00. The results of the study shows that on the interaction between initiating structure and consideration to job satisfaction significance at the level of 0,044. This shows that there are significant differences in the job satisfaction in terms of the interaction between initiating structure leadership style and consideration. Keyword : Initiang Structure, Consideration, Job Satisfaction